Development of Pc-Based Multi-Channel Measurement Unit - Omer, Abdu Idris (1997)
Nowadays the microcomputer has been involved in a variety of applications. These applications range from a simple ON/OFF operation to intelligent data acquisition, signal processing and control in individual automation applications. Moreover it can be utilised in monitoring different physical and electrical quantities. This study was mainly concerned with the design of 2-channel isolated current measurement board. The board can be plugged into one of the input/output (I/O) slots in the IBMlPC/ AT or compatibles. Signal from enzyme electrodes were used in the analysis to monitor the oxygen consumption or the production of hydrogen peroxide that represented the input current to the board. Each channel was selected using a software.